Examining Income Patterns and Time Allocation in Nutmeg (Myristica Fragrans) Farmint: A Case Study of Padang Selatan District, Padang, West Sumatra, Indonesia - Evaliza, Dwi; Tanjung, Faidil; Azhari, Rafnel (Universitas Andalas, 2023)
This research aims to determine the income and profits of Pala (Myristica Fragrans) Â products and analyze the working time allocation in producing Pala products in Padang Selatan District. The study was conducted from September to November 2022. The research method used was descriptive with a survey approach. The data collected consists of two types, namely primary data and secondary data. The selction of respondent is done by simple random sampling method. The samples were 34 farmers. From the Pala tree the farmers can harvest the seeds, mace, and fruit meat which was processed into Pala syrup. The products most widely used by farmers are seeds and mace. From on the three Pala products produced, the highest average income is from the seed with an average income of Rp. 3,209,252 (70.53%), followed by Pala syrup of Rp. 767,310 (16.86%) and the lowest income is mace products which was 573,356 (12.60%). The highest working time allocation was found in processing of Pala seed products which was 8.85 working time allocation / year (54.16%), mace products of 5.83 working time allocation / year (35.68%) and the lowest in Pala syrup products of 1.66 working time allocation / year (10.16%). The Â farmers should cultivate Pala in accordance with the recommendations, as well as processing the fruit meat into various preparations so that farmers' income can increase.Keywords: Income analysis, working time, pala